PENGARUH EFIKASI DIRI, SKEPTISISME PROFESSIONAL DAN FEE AUDIT TERHADAP KUALITAS AUDIT (STUDI DI KAP KOTA BANDUNG) - Ruseka, Fahmi Damarjati; Ismail, Muhammad Taofik; Handayani, Wuri; Hidayat, Syarief (Universitas Sangga Buana, 2024)
The number of cases that befell accounting firm in Indonesia caused by the poor quality of the audit report results have an impact on the loss of public confidence in the results provided by the accounting firm. This study was conducted to determine the variables of self-efficacy, professional skepticism and audit fees on the quality of audits conducted at Accounting Firm in Bandung. The population in this study were 155 people from 9 Public Accounting Firms with stratified sampling technique. The results show that the variables of self-efficacy, professional skepticism and audit fees have an effect on audit quality at Accounting Firm in Bandung City.